Analysis of The Implementation of Digital Marketing for Marning SMEs in Bukit Barisan Village, Merigi District - Beatrix Tandyana; Eva Angelique; Cicilia Rahayuning Tyas Utami; Damar Aryo Puntodewo; Arie Vatresia (International Journal Labs, 2026)
Digital marketing has become an essential strategy for strengthening the competitiveness of micro, small, and medium enterprises, particularly rural food-based businesses that still depend on conventional marketing systems. This study aims to analyze the implementation of digital marketing among marning SMEs in Bukit Barisan Village, Merigi District, by identifying adoption levels, inhibiting factors, and strategic business opportunities. This research employed a descriptive qualitative method through observation, interviews, questionnaires, documentation, and mentoring activities involving marning business actors, with a specific focus on Sifa Rasa Shop. The analysis used the 7P marketing mix and SWOT approach to evaluate internal strengths, weaknesses, external opportunities, and threats. The results show that digital marketing adoption remains limited. Of 22 identified business actors, only 11 participated in training, seven were interested in mentoring, and only two implemented digital marketing through platforms such as Instagram, TikTok, and Shopee. Major barriers included low digital literacy, product legality and certification limitations, packaging problems, dependence on traditional sales, and limited managerial readiness. However, Sifa Rasa Shop demonstrated strong potential through product variety, competitive pricing, legality, attractive packaging, and marketplace utilization. In conclusion, digital marketing implementation is still transitional but promising when supported by structured training, mentoring, product legality, and continuous digital capacity building.